Rekonseptualisasi Definisi dan Peran Strategis Manajemen Perpustakaan Pondok Pesantren di Era Digital - Zaky Dhiaulhaq Rahman; Fauziah, Siti Syifa; Zohriah, Anis; Bachtiar, Machdum (Literatify : Trends in Library Developments, 2025)
The rapid changes in the digital era require a reconceptualization of library management, including in Islamic boarding schools. This article examines the definition and strategic role of pesantren library management in a digital context, based on the literature of the last 3-5 years. Through literature studies and qualitative content analysis from Google Scholar, SINTA, and DOAJ, it was found that the role of pesantren libraries has shifted from managing physical collections to facilitating ethical and curated digital knowledge access. The pesantren library has now evolved into a comprehensive digital literacy facilitator, a digital Islamic learning resource center, a curator of Islamic content, a global information network link, a supporter of learning innovation, and a center for the development of students’ digital learning communities. This reconceptualization accommodates the unique needs of Islamic boarding schools, such as digitization of yellow books and manuscripts, the development of students’ digital skills for study and da’wah, and the strengthening of digital-based traditional learning communities. Despite the challenges of digital divides, human resources, and funding, the opportunities for improving access to information, preserving intellectual heritage, and quality of education are enormous. The implication is the need to improve managers’ competence, leadership policy support, and strategic investment to realize a transformative digital pesantren library.